2018
DOI: 10.1111/jcpt.12674
|View full text |Cite
|
Sign up to set email alerts
|

Stability of dobutamine in continuous ambulatory delivery devices

Abstract: Our findings will allow health professionals to provide a weekly supply of dobutamine-containing CADDs to patients for home infusions. Continuous infusion over a 24-hour period using one CADD per day will also decrease the number of exchanges required and thus reduce the risk of catheter-related bloodstream infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Our study also shows that pH decreased with increasing drug concentration, which is consistent with findings from a previous study . Furthermore, it was reported that the delta pH was <0.2 (our study: delta pH ≤ 0.12), indicating essentially unchanged pH . The admixture appearance and pH measurement indicated that etoposide, epirubicin hydrochloride and vindesine sulphate were physically compatible in the admixtures …”
Section: Discussionsupporting
confidence: 92%
“…Our study also shows that pH decreased with increasing drug concentration, which is consistent with findings from a previous study . Furthermore, it was reported that the delta pH was <0.2 (our study: delta pH ≤ 0.12), indicating essentially unchanged pH . The admixture appearance and pH measurement indicated that etoposide, epirubicin hydrochloride and vindesine sulphate were physically compatible in the admixtures …”
Section: Discussionsupporting
confidence: 92%